Gender-Based Violence In Bangladesh: A Critical Analysis - Md. Abu Shahen (International Journal of Qualitative Research, 2021)
This study tried to explore the current nature of gender-based violence and harassment in Bangladesh. Specifically, gender-related harassment and discrimination with violence against women and children have been explored throughout the study. However, the study is based on secondary data collected from gender-focused scholars and organizations. The data of ASK and BSAF have been used for critical analysis regarding violence, harassment, and discrimination against women and children in Bangladesh. As findings, the study found that the prevalence of domestic violence and oppression against wife and housemate including cleaner, housekeeping, and cooker have existed in the forms of torture, negligence, rape, forced rape, physical assault, and sexual assault. The study also found that women and girls are being harassed in transportation as they feel unsecured in movement through abusive and negative attitudes and behavior such as touching, closely standing, intentionally pushing, and gripping in shoulders, bad beckon and comment, and touching in the sensitive part of the body. It is also seen that the business environment is not favorable for women Entrepreneurs due to constraints social and cultural attitudes, lack of political commitment, and insufficient governmental provisions for establishing a women-friendly business environment.